2019
DOI: 10.1002/adom.201900276
|View full text |Cite
|
Sign up to set email alerts
|

Surface Halogen Compensation for Robust Performance Enhancements of CsPbX3 Perovskite Quantum Dots

Abstract: Understanding the subtle structure–property relationships of quantum dots (QDs) is essential for targeted modulation of optoelectronic properties, and the influences of surface defects of inorganic halide perovskite (HP) QDs are still not very clear. Here, the negative exciton trapping effects of surface halide vacancies (VX) on the photoluminescence quantum yield QY (PLQY) of HPQDs are determined by a detailed analysis of the optical parameters, exciton dynamics, and surface chemical states. Based on the fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
118
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 161 publications
(122 citation statements)
references
References 56 publications
3
118
0
1
Order By: Relevance
“…On one hand, CsPbBr 3 QDs are terminated with bromide ions and the ammonium interacts with bromide atoms through hydrogen bonds . The formation of hydrogen bonds reduces the coulombic interactions between lead and bromide ions, and then ammonium ligands will fall off from the QD surface along with bromide ions ( Scheme a left) . On the other hand, the deprotonated ammonium ligands cannot interact with the CsPbBr 3 QDs.…”
Section: Methodsmentioning
confidence: 99%
“…On one hand, CsPbBr 3 QDs are terminated with bromide ions and the ammonium interacts with bromide atoms through hydrogen bonds . The formation of hydrogen bonds reduces the coulombic interactions between lead and bromide ions, and then ammonium ligands will fall off from the QD surface along with bromide ions ( Scheme a left) . On the other hand, the deprotonated ammonium ligands cannot interact with the CsPbBr 3 QDs.…”
Section: Methodsmentioning
confidence: 99%
“…For example, high‐quality OIHP nanocrystals (NCs) with near‐unity PL QY and narrow full width at half maximum (FWHM) could cover the full visible range via either in situ passivation or posttreatment methods. [ 14–19 ] In addition, the external quantum efficiency (EQE) of OIHP LEDs have been promoted to over 20% in green, red, and near‐infrared radiation regions. [ 1,20,21 ] It has been concluded that the high symmetry of the cubic lattice and unique electronic configuration of Pb 2+ (d 10 s 2 ) with inactive 6p orbits play critical roles in determining the optoelectronic properties of OIHPs.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Currently, CsPbX 3 (with X being single or mixed Cl, Br, and I anions) perovskite quantum dots (QDs) are the most frequently investigated systems because of their high PL quantum yield (PLQY) and chromatogram purity, low-threshold lasing, as well as sharp emission line-width. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Unfortunately, CsPbX 3 perovskite QDs are sensitive to the external environments such as polar solvents, moisture, heat, and light, which usually destroy their structure and degrade their performances. [21][22][23][24][25][26][27][28] These issues greatly impede their developments towards practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…All‐inorganic luminescent perovskite materials have been an active research area in recent years for their superior photoluminescence (PL) properties and potential applications in display, lighting, light‐emitting diodes, optoelectronic detector, lasing, anti‐counterfeiting code, etc . Currently, CsPbX 3 (with X being single or mixed Cl, Br, and I anions) perovskite quantum dots (QDs) are the most frequently investigated systems because of their high PL quantum yield (PLQY) and chromatogram purity, low‐threshold lasing, as well as sharp emission line‐width . Unfortunately, CsPbX 3 perovskite QDs are sensitive to the external environments such as polar solvents, moisture, heat, and light, which usually destroy their structure and degrade their performances .…”
Section: Introductionmentioning
confidence: 99%